Low-income, yet highly literate? the future towards developing a ‘super smart society’ - Mohd Nor Shahizan Ali,; Neesa Ameera Mohamed Salim,; Petrus Ana Andung,; Felisianus Efrem Jelahut,; Maria V.D. Pabha Swan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The low-income community is generally associated with a lower level of education, poor quality housing, unemployment, and financial debt. As digital technologies become increasingly integrated into society, this study aims to re-examine the understanding of advertising literacy within low-income communities by introducing digital literacy as a new dimension. The focus is on assessing their awareness of visual pollutants, specifically fly-poster, in Malaysia. The study involved 574 respondents from five Public Housing Programs (PHP) to represent the distribution of the low-income community. The study combined media literacy theory and the model of advertising literacy. Results indicated that individuals in the low-income community exhibit high advertising literacy influenced by digital technological factors, empowering them to make informed decisions amidst the deluge of advertisements. Despite this, the challenge of visual pollutants remains unresolved due to the insufficient efficacy of collective actions by the community, hindering efforts to mitigate their impact on the local environment. To embrace the future of a 'super smart society,' the low-income community must collectively adapt and adopt digital technologies. This study contributes to the discourse on the importance of digital literacy and collaborative efforts in shaping an intelligent society, often referred to as Society 5.0 or the 'super smart society.'